1970
DOI: 10.4314/bajopas.v4i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Phytochemical Screening and Antimicrobial Activities of Some Medicinal Plants Used In Ebiraland

Abstract: Dried leaves of Abrus precatorius, Desmodium ramosissimum, Scoparia dulcis and aerial parts of Phyllanthus amarus used in folkloric medicine of Ebiraland were extracted with hexane, methanol and water sequentially using soxhlet apparatus. The extracts were screened for antimicrobial activities against Bacillus subtilis, E. coli, Pseudomonas aeruginosa, Salmonella typhi, Staphylococcus aureus and Candida albicans using the agar-cup diffusion protocol. All the extracts except the hexane extract of Abrus precator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The antimicrobial activities of all the synthesized compounds were determined by the agar cup diffusion technique [ 53 ]. The nutrient agar and SDA plates were inoculated with 0.1 mL broth culture of the test bacteria or fungi.…”
Section: Methodsmentioning
confidence: 99%
“…The antimicrobial activities of all the synthesized compounds were determined by the agar cup diffusion technique [ 53 ]. The nutrient agar and SDA plates were inoculated with 0.1 mL broth culture of the test bacteria or fungi.…”
Section: Methodsmentioning
confidence: 99%
“…The methanolic extract of P. amarus also showed a broad spectrum of activity with a minimum inhibitory concentration of 1.56 mg/mL against all the test microorganisms. The extracts were also screened for secondary metabolites and the result indicated the presence of alkaloids, saponins, tannins and terpenoids (Alli et al, 2011). The 80% methanolic extracts obtained from seven Phyllanthus sp.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Unlike our study, which found that P. amarus AE was more effective against L. interrogans than ME, other studies have reported that MEs are more effective than AEs against other bacteria, as well as fungi. MEs of aerial parts of the plant have shown more potent inhibitory effects against Bacillus subtilis , Escherichia coli , Pseudomonas aeruginosa , Staphylococcus aureus , Salmonella serotype Typhi, and Candida albicans than AEs [ 26 ]. Similarly, Sen and Batra reported that aqueous leaf extracts exhibited minimal activity against B .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found slight differences in phytochemical contents between AEs and MEs. Phytochemical analyses of AEs have detected the presence of primary (carbohydrates, proteins, and amino acids) and secondary metabolites (anthraquinone, steroids, including phytosterols and cardiac glycosides, alkaloids, terpenoids, including triterpenes and saponins, phenolic compounds, including flavonoids and lignins, and tannins, specifically phlobatannins) [ 12 , 16 , 17 , 26 , 29 , 30 ]. Analyses of MEs have revealed the presence of carbohydrates, alkaloids, saponins, terpenoids (triterpenes), steroids (cardiac glycosides), phenolic compounds (flavonoids), and tannins (phlobatannins) [ 12 , 16 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%